Theoretical Analyses of Glibenclamide-Estradiol Derivative and Its Relationship with Some Physico-chemical Descriptors - Figueroa-Valverde, L.; Díaz-Cedillo, F.; López-Ramos, M.; García-Cervera, E.; Pool Gómez, E. (Asian Journal of Chemistry, 2012)
A new glibenclamide-estradiol conjugate was synthesized by the reaction of glibenclamidesuccinate and estradiol-ethylenediamine derivative using N,N'-diciclohexylcarbodiimide/p-toluensulfonic acid as catalysts. In order to evaluate the degree of lipophilicity and its relationship with some physicochemical descriptors involved in its chemical structure, the ACD log P and KOWWIN methods were used. The results showed an increase in the values of these physicochemical parameters for the glibenclamide-estradiol conjugate in comparison with glibenclamide and glibenclamide-succinate. These data suggest a relationship between the evaluated physicochemical parameters and the degree of lipophilicity of the glibenclamide-estradiol conjugate.